The influence of organizational culture and gender salience on managers' decision-making styles - Romaine, Janet (My University, 1999)
A number of studies have established that women in managerial positions are more likely to be participative (involving subordinates in their decision-making) than their male counterparts. The present research was designed to address the question of whether certain antecedent conditions--in particular, features of organizational culture--affect the degree to which women and men differ in participative behaviour. This question is important for several reasons: scientific understanding (since gender-based differences, especially behavioural ones, are little understood), development of organizational theory, and greater understanding for practitioners of how participative managerial styles can be fostered. The research design is a field study, utilizing a combination of quantitative and qualitative measures. While this design created a number of constraints, I believe that it was useful in terms of trustworthiness of the findings. The naturalistic setting and the opportunity to triangulate the findings were among the advantages of the research design; disadvantages included a necessarily small sample size, and purposive sampling limited by the ability and willingness of organizational gatekeepers and members to take part in the research. The central focus of investigation was whether and how organizational culture influences participative behaviour for women managers. The initial model proposed that in traditional organizations, gender salience is heightened for women in managerial roles because of their scarcity and because managerial stereotypes tend to involve traits generally perceived (in North American culture) as masculine. Findings showed that heightened gender salience accounted for at least part of the observed gender difference in participative behaviour. The findings of the research at first seemed paradoxical, since the organization which was the least traditional (i.e., the most woman-friendly in its policies) was also the one in which gender salience seemed to be high compared to the rest of the sample. This finding led to a modification of the original model to a more complex, time-dependent understanding of the process under study.
Keywords: Business Administration, Management, and Operations; Business Administration, Management, and Operations